Islam and Environment: Education Perspective - Fathil, Mohd.; Saam, Zulfan; Sukendi, Sukendi; Nizar, Syamsul (AT-TA'LIM, 2015)
A Muslim views that nature belongs to God and human beings must show that they are grateful by learning how to use and manage it well so that it can provide benefits to the mankind. Exploiting nature taught by Islam is based on the utilization of responsibility that provides benefits not only for its content but also its intact and sustainable opportunities to cultivate and for rehabilitation or to help speed up its recovery. Humans are required to have certain characters towards nature, which means dealing with nature by maintaining sustainability. Therefore, God gives cues to enable people to control themselves in exploitation of the natural resources which causes defection that can harm and even destroy human life. For that reason, Islam forbids destructing or harming the environment ranging from very small actions and trivial such as prohibiting throwing human faces under a fruit tree, in the river, on the road, or in the shelter areas. Prophet Muhammad (PBUH) is also very concerned about the preservation of wildlife, as described in the Hadith narrated by Abu Dawood. Even Prophet never reprimanded one of his companions during the Hijrah period to take the chicks out of the nest. Similarly, Islam cares about the environment created by God which human beings are mandated to maintain nature properly and responsibly.Â Keywords: Concept of Islam, the environment, education.Copyright Â© 2015 by Al-Ta'lim All right reserved